Age-associated and breed-associated variations in haematological and biochemical variables in young labrador retriever and miniature schnauzer dogs - Brenten, Thomas (Vet Rec Open, 2016)
Breed, sex and age effects on haematological and biochemical variables were investigated in 24 labrador retriever and 25 miniature schnauzer dogs during the first year of life. Blood samples were taken regularly between weeks 8 and 52. White blood cell and red blood cell counts, haemoglobin concentration, haematocrit, mean cell volume, mean cell haemoglobin, mean cell haemoglobin concentration, platelet count as well as total protein, albumin, calcium, phosphate, alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase, glutamate dehydrogenase, total cholesterol, triglycerides, creatine and urea were evaluated. For all haematological and biochemical parameters, there were significant effects of age on test results. Statistically significant effects for breed and the breed×age interaction on test results were observed for most of the parameters with the exception of haemoglobin. Variations in test results illustrate growth related alterations in body tissue and metabolism leading to dynamic and marked changes in haematological and biochemical parameters, which have to be considered for the interpretation of clinical data obtained from dogs in the first year of life.